Environmental monitoring and characterization - Artiola, Janick F.; Pepper, Ian L.; Brusseau, Mark L. (Amsterdam ; Boston : Elsevier Academic Press, 2004)
Environmental Monitoring and Characterization is an integrated, hands-on resource for monitoring all aspects of the environment. Sample collection methods and relevant physical, chemical and biological processes necessary to characterize the environment are brought together in twenty chapters which cover: sample collection methods, monitoring terrestrial, aquatic and air environments, and relevant chemical, physical and biological processes and contaminants. This book will serve as an authoritative reference for advanced students and environmental professionals. * Examines the integration of physical, chemical, and biological processes * Emphasizes field methods and real-time data acquisition, made more accessible with case studies, problems, calculations, and questions * Includes four color illustrations throughout the text * Brings together the concepts of environmental monitoring and site characterization.
1 Monitoring and Characterization of the Environment -- 2 Sampling and Data Quality Objectives in Environmental Monitoring -- 3 Statistics and Geostatistics in Environmental Monitoring -- 4 Automated Data Acquisition and Processing -- 5 Maps in Environmental Monitoring -- 6 Geographic Information Systems and Their Use for Environmental Monitoring -- 7 Soil and Vadose Zone Sampling -- 8 Groundwater Sampling -- 9 Monitoring Surface Waters -- 10 Monitoring Near-Surface Air Quality -- 11 Remote Sensing for Environmental Monitoring -- 12 Environmental Physical Properties and Processes -- 13 Chemical Properties and Processes -- 14 Environmental Microbial Properties and Processes -- 15 Physical Contaminants -- 16 Chemical Contaminants -- 17 Microbial Contaminants -- 18 Soil and Groundwater Remediation -- 19 Ecological Restoration -- 20 Risk Assessment and Environmental Regulations.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Environmental monitoring; Environnement -- Surveillance; Electronic books